An enquiry concerning the principles of cultural norms and values: The impact of uncertainty and mortality salience on reactions to violations and bolstering of cultural worldviews - van den Bos, Kees; Poortvliet, P. Marijn; Maas, Marjolein; Miedema, Joost; van den Ham, Ernst-Jan (Journal of experimental social psychology, 2005)
This enquiry concerning the principles of cultural norms and values focuses on the impact of mortality and uncertainty salience on people’s reactions to events that violate or bolster their cultural norms and values. Five experiments show that both mortality and uncertainty salience influence people’s reactions to violations and bolstering of their cultural worldviews, yielding evidence for both terror and uncertainty management theories. Interestingly, the five experiments consistently reveal that uncertainty salience has a bigger impact on people’s reactions than mortality salience, suggesting that the former may be a more important antecedent of reactions to norms and values than the latter. Findings further suggest that uncertainty salience did not instigate death-thoughts whereas reactions to norms and values were stronger among mortality salient participants who thought of uncertainty as a result of the mortality salience manipulation than mortality salient participants who did not think of uncertainty following this manipulation. Implications are discussed.